2018
DOI: 10.1111/jsr.12810
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in patients with implantable cardioverter defibrillators: Associations with objective sleep duration, age and anxiety

Abstract: Sleep disturbance and anxiety are highly prevalent in patients with implantable cardiac defibrillators (ICDs). There is limited research, however, on the associations between cognitive performance and sleep parameters, age and anxiety. Forty‐one patients with ICDs and self‐reported sleep disturbance completed 14 days of actigraphy (Mage = 60.3, SD = 12.3) measuring total sleep time (TST), and a computerized cognitive test battery measuring processing speed and attention (i.e. simple reaction time and symbol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 52 Five studies demonstrated that sleep behavior and PA were associated with patient-reported physical function, quality of life, and cognitive function. 49 , 52 , 53 , 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 52 Five studies demonstrated that sleep behavior and PA were associated with patient-reported physical function, quality of life, and cognitive function. 49 , 52 , 53 , 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…studies) References Low physical activity Increased risk of hospitalization and mortality 286 RCT substudy (2); Prospective observational (1). 56 , 57 , 58 HF patients engage in low-intensity activity, have a poor objective sleep continuity and flat circadian rhythmicity N/A 174 Cross-sectional (3); 45 , 46 , 74 Step count and MVPA associated with NYHA class and LVEF † N/A 456 RCT substudy (1); Cross-sectional (2); Pilot study (1); Feasibility study (1) 48 , 49 , 50 , 51 , 52 High step count, MVPA, and sleep time associated with patient-reported QoL, functional status, and cognitive function N/A 331 RCT substudy (3); Feasibility study (1); Cross-sectional (1) 49 , 52 , 53 , 54 , 55 HF = heart failure; ICD = implantable cardioverter-defibrillator; LVEF = left ventricular ejection fraction; MVPA = moderate–to-vigorous physical activity; N/A = not applicable; NYHA = New York Heart Association; PA = physical activity; QoL = quality of life; RCT = randomized controlled trial. † Witham et al did not show an association between NYHA class and accelerometry counts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of a lack of independent associations between sleep efficiency, TST, and pain with cognitive performance (reasoning, working memory, attention, and processing speed) is generally inconsistent with findings in other populations (eg, healthy older adults, middle-aged and older adult cardiac patients). 1,2,4,5,12 These prior studies have generally showed better sleep efficiency, both long and short sleep duration, and less pain, are associated with better cognitive performance, typically in executive functions. However, it is possible that in middle-aged and older adults who are sedentary, sleep efficiency and TST are only associated with cognition in the context of other poor health factors such as pain (or vice versa), underscoring the need to examine these factors in such investigations.…”
Section: Discussionmentioning
confidence: 99%
“…11 We also previously showed that longer TST (as assessed by actigraphy) was associated with better processing speed and attention in primarily middle-aged and older cardiac patients with implantable cardioverter defibrillators. 12 Although some studies show a curvilinear relationship between TST and cognitive performance (ie, both long and short TST are associated with worse cognition) across a range of tasks, 13,14 another study suggests that the curvilinear relationship between TST and cognition may only be observed in younger and older adults and not in middle-aged adults. 15 Taken together, there are numerous studies evaluating the independent associations between sleep efficiency, TST, and cognition.…”
Section: Introductionmentioning
confidence: 99%